PERANAN UNIT RESERSE KRIMINAL DALAM MENGUNGKAP TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN DI WILAYAH HUKUM KEPOLISIAN SEKTOR BUKIT RAYA - Silaban, Lamtiar; Lestari, Rika; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The increasing amount of crime that happens, especially the crime of theft by weighting in the jurisdiction of the Police Sector Bukit Raya, padatahun 2011-2012, has caused unrest in the society. Though the police as law enforcement agencies in carrying out their duties remain subject to and comply with the duties and authority as stipulated in Law No. 2 of 2002 on the Police to maintain security and public order, enforce the law and provide protection, guidance, and service to the community. In this case the role of the Criminal Investigation Unit had not been optimal. This is because there are still many obstacles faced by the Criminal Investigation Unit.This type of research is empirical juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study.From the research, there are three main problems that can be inferred. The first role of the Police Criminal Investigation Unit investigators Bukit Raya sector in exposing the crime of theft by weighting has not run optimally, this is because there are some in practice. The second obstacle faced by the Criminal Investigation Unit of the Police Sector Bukit Raya in exposing the crime of theft by weighting, is as follows, the first factor means and inadequate infrastructures, both public factors, the absence of a third suspect or the difficulty of disclosure of evidence the crime of theft by weighting has been undermined because he suspects fled the scene as well. Third Efforts are being made to overcome the barriers faced by the Criminal Investigation Unit of the Police Sector Bukit Raya in exposing the crime of theft by weighting is as follows, look for alternative facilities and infrastructure are inadequate, entered into a collaboration with the community through legal counseling, manufacture and conduct patrolling post patrols in crime-prone areas, as well as publishes wanted list. Advice Author, First, The Role of the Criminal Investigation Unit of the Police Sector Bukit Raya in uncovering criminal acts, especially the crime of theft by weighting, should be further enhanced, the Second, To the government, particularly the Indonesian National Police investigation budget to increase the number of facilities and infrastructure required by Sector Police Criminal Investigation Unit Bukit Raya, Third, need to improve public awareness of the law.